A szervezettség és a humán erőforrások változása 5 év tükrében - Vántus, András (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
It is more and more important to reduce the costs of production as much as possible at farming organizations last years - especially - in unfavourable economic and financial surroundings. This statement is true for cattle farming branches mainly for diary farms. Arising of this situation it is needed to study farming and carry out the possible rationaliza-tion after analyzing. The author surveyed diary farms in Hajdú-Bihar County in order to reveal the situation and the taken steps to save their competitiveness. He worked at chang-ing of workers number, qualifications, the duration of workers’ professional practice and the size of cattle herd. Methodical observation and oral interviews were used to the studies. Indexes of labour productivities were counted using the mentioned data. These indexes symbolize the favourable effects of the management’s arrangements.